The reversed bell‐bottom technique (ReBel‐B) for the endovascular treatment of iliac artery aneurysms. Issue 4 (18th July 2020) - Mazzaccaro, Daniela; Righini, Paolo; Zuccon, Gianmarco; Modafferi, Alfredo; Malacrida, Giovanni; Nano, Giovanni
Abstract: Objective: To describe the results of the reversed bell‐bottom (ReBel‐B) technique for the endovascular treatment of iliac aneurysms (IA) involving the origin of hypogastric artery (HA). Methods: The ReBel‐B technique is a strategy for the occlusion of HA in selected patients presenting with IA, in whom the HA cannot be spared or safely occluded with coils or vascular plugs. When employing this technique, an iliac flared ("bell‐bottom") extension is deployed in a reverse fashion, through a contralateral crossover femoral access that allows the occlusion of the HA at its origin, by exploiting the flared "bell" part of the reversed endograft. A second limb is then deployed to complete the implant, from the common iliac to the external iliac artery, inside the previous graft. Data of all consecutive patients treated with this technique in our experience were then retrospectively reviewed, and outcomes analyzed. Results: The ReBel‐B technique was employed in total of six patients who came in an emergent setting for the rupture of a common IA, from January 2014 to December 2018. Endovascular exclusion was performed using a ReBel‐B graft plus iliac leg in five out of six cases. In the remaining case, a bifurcated aortic endograft was used to complete the aneurysm exclusion. Technical success was 100%. No complications occurred. Conclusions: In selected cases, the ReBel‐B technique can be used for the complete exclusion of IA preventing type II endoleak from the HA, when the embolization with coils or plug or the preservation of the HA is anatomically unfeasible.